Anti-termite activity of essential oil and its components from Myristica fragrans against Microcerotermes beesoni - Mahesh Pal; Rajesh Kumar; Sri Krishan Tewari (Journal of Applied Sciences and Environmental Management)
The essential oil obtained by hydrodistillation of the fruits of Myristica fragrans was analyzed by GC and GC-MS. Twenty eight compounds were identified representing 95.9% of the oil. The major constituents of the oil were α-pinene (6.4%), Sabinene (37.7%), β-pinene (7.3%), myrcene (3.5%),Limonene (4.7%),Terpine-4-ol (5.8%), safrole (3.4%) and myristicin (6.8%).The essential oil and its major constituents were evaluated at different dilution against Microcerotermes beesoni, test termite. The LC50 value of fruit essential oil is 28.6 mg/g. Furthermore, exposure to myristicin caused 100% mortality at a dosage of 5 mg/g after 14d. @JASEM